The South African Construction Industry: Perceptions Of Key Challenges Facing Its Performance, Development And Growth - Windapo, Abimbola Olukemi; Cattell , Keith (Penerbit Universiti Sains Malaysia, 2013)
The paper investigates the challenges influencing the performance, development and growth of the South African construction industry. The paper examines whether there is a key challenge perceived by construction industry stakeholders as affecting the development and growth of the sector. The rationale for the examination stems from the varied and largely unexamined assumptions available in the literature as to what the key challenge is. The research adopts a qualitative approach, using semi-structured interviews of 120 construction industry stakeholders based in Cape Town. The respondents were selected using the convenience and snowball sampling technique. The results of the study show that from a ranking perspective, the key challenges perceived by stakeholders as affecting the performance, development and growth of the construction industry in South Africa include the increasing costs of building materials, access to mortgage/credits, high interest rates and the high rate of failure of contracting enterprises. The paper concludes that to foster construction industry performance and growth in South Africa, there must be further studies to identify the factors responsible for the increases in the costs of building materials and to test the assumption that exploration and development of new materials and technologies, rather than exploitation of existing ones, will ensure stable building material prices.